Unilateral pulmonary vein atresia presenting with recurrent haemoptysis in a child : a case report - Martin Ngie, Liong Wong; Tang, Ing Ping; Chor, Yek Kee; Lau, Kiew Siong; Anne Rachel, John; Hii, King Ching; Olive Pei, Yi Lee; Lim, Wooi Kok; Hannah Pei, Koon Tan (BioMed Central Ltd., 2021)
Background: Haemoptysis is an uncommon presenting symptom in children and is usually caused by acute lower respiratory tract infection or foreign body aspiration. We report a rare case of right unilateral pulmonary vein atresia (PVA) as the underlying aetiology of recurrent haemoptysis in a child. Case presentation: A 4 years old girl presented with history of recurrent haemoptysis. Bronchoscopic evaluation excluded a foreign body aspiration but revealed right bronchial mucosal hyperaemia and varices. Diagnosis of right unilateral PVA was suspected on transthoracic echocardiography which demonstrated hypoplastic right pulmonary artery and non-visualization of right pulmonary veins. Final diagnosis was confirmed on cardiac CT angiography. A conservative treatment approach was opted with consideration for pneumonectomy in future when she is older. Conclusion: Rarer causes should be considered when investigating for recurrent haemoptysis in children. Bronchoscopy and cardiac imaging are useful tools to establish the diagnosis of unilateral PVA in our case.